The Capacocha: Mechanism and function of human sacrifice, its geometric projection, its role in integrationist politics and in the redistributive economy of Tawantinsuyu - Duviols, Pierre (1976)
The manuals or treatises on Inca civilization do not generally mention the rites of capacocha, perhaps because there is no monograph on this subject that has collected the scattered data in ethnohistorical sources. However, it is worth looking closely at this issue. One realizes that the capacocha was one of the most solemn ceremonies of Inca life and in which the largest number of individuals of the entire "empire" participated. Still 89 years after the Conquest, populations far removed from Cusco preserved the memory of what had been. In addition, the reconstruction of the facts as far as we can take it -and the analysis- of its operation and purposes, convinces that we are facing one of the most original institutions of the Tawantinsuyu, especially significant in terms of the mechanisms of political, social and cultural reciprocity. put into play and that, therefore, helps us to better understand those mechanisms.